VIEWS OF ELEMENTARY EDUCATION STUDENTS AT TERTIARY LEVEL ABOUT THE METHODS AND TECHNIQUES USED IN ATATÜRK'S PRINCIPLES AND REVOLUTION COURSE - Gulay Saricoban (Informascope, 2018)
This study examines elementary education department students' view about the methods and techniques generally preferred by their instructors in teaching The History of Atatürk's Principles and Revolution I and II courses. For the purpose of the study, the questionnaire (r=.90), investigating the methodological and technical skills of instructors, developed by Çelikkaya and Kuş (2009) has been administered to 1st (n=105) and 4th (n=123) year elementary education students in the faculty of education at a public university. Descriptive statistics has been used to analyze the data about the views of the elementary education students who participated in the study about The History of Atatürk's Principles and Revolution I and II courses in terms of use of methods and techniques used by the instructors.  Relying on the findings obtained at the end of the study, the participants reported generally negative views about their instructors' methods and techniques in The History of Atatürk's Principles and Revolution course, however, they draw attention to the points such as use of technological aids, students' presentations, feedback, opportunity projects, opportunity for students asking and answering questions both by the instructor and their peers, forming group works, and letting discussions in the classroom about the topics under discussions.